1987
DOI: 10.2307/3899363
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Relationships among Feral Horses, Cattle, and Pronghorn in Southeastern Oregon

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press and Society for Range Management are collaborating with JSTOR to digitize, preserve and extend access to Journal of Range Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
4
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 34 publications
2
31
4
3
Order By: Relevance
“…Consumption of sagebrush may also be influencing its recruitment as feral horses will consume small quantities of sagebrush, though they primarily consume grass (Krysl et al 1984, McInnis andVavra 1987). In contrast to our results, Beever et al (2008) did not find a difference in sagebrush frequency between horse grazed and horse removed areas.…”
Section: Discussioncontrasting
confidence: 78%
“…Consumption of sagebrush may also be influencing its recruitment as feral horses will consume small quantities of sagebrush, though they primarily consume grass (Krysl et al 1984, McInnis andVavra 1987). In contrast to our results, Beever et al (2008) did not find a difference in sagebrush frequency between horse grazed and horse removed areas.…”
Section: Discussioncontrasting
confidence: 78%
“…In other words during our sampling period, available forage was CP deficient for about 32 days (mid Septemberearly October) in 1992 and 134 days (late July-November) in 1993. Large herbivores typically harvest diets of higher quality than hand-compounded rations or wholeplant samples (Kiesling et al 1969, McInnis and Vavra 1987, Cruz and Ganskopp 1998, so adequate CP concentrations probably extend for longer periods of time in applied situations.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace et al (1961) described in vitro cellulose digestibility of 6 grasses from 30 May to 5 September, with values ranging from a high of 76% to a low of 37% late in the season. Raleigh (1970) and McInnis and Vavra (1987) monitored nutritional indices of grasses from late April to early September and noted that forage quality began deteriorating even before stems started elongating in the spring. Quality continues to decline until early August when forages mature and dry (Raleigh 1970, Murray et al 1978.…”
Section: Introductionmentioning
confidence: 99%
“…Duncan (1992) showed that domestic horses in the French Camargue Park like eating grasses and Chenopodiaceae. McInnis and Vavra (1987) concluded that the North American mustang chooses mainly Poaceae and Chenopodiaceae brome saltbush and other plants for food. Meng (2007) and Chen (2008) showed that KNR Przewalski's horses preferred Gobi Stipa and Ceratoides.…”
Section: Clustering and Categorization Of Vegetation Patchesmentioning
confidence: 99%